ADE533: Design and Visual Communication / Faculty of Education - UiTM, Faculty of Education (2021)
Design and Visual Communication addresses the connections between visual perception, cognition, and communication in contemporary Regional society. The course is designed to provide students with an overview of the importance of visual perception to cognition and conceptualization. Student will be introducing to semiotic theory, an examination of media ecology, and understanding of the relationship between visual media and issues of identity, community, and culture. These courses also enhance student critical perspective on the use of Visual Communication in local issues and news media of Corporate Identity. While being introduced to vital theoretical concepts, students should come to a more critical understanding of the role of visual media and technology in contemporary society and the interplay of cultures in Packaging and Advertising.